Image versus writing:: from post-graffiti and murals’ assault to graffiti’s scriptural riposte in Madrid, Spain - Garcia, Lisa (SAUC - Street Art and Urban Creativity (repository), 2018)
The 2010s have witnessed the rise of a new aspect of street art on the world stage: institutionalized murals. Downtown Madrid is no exception, though the mural scene there remains less developed than in some other European cities like Saragossa or Paris. Forsaking its graffiti forbear’s emphasis on writing, this new trend embraces instead the power of imagery. Meanwhile in the walls of central Madrid, the writers are showing a new resilience with a variety of strategies that will ensure that the written word survives the ascent of the image in street art. This leads to a plastic discord juxtaposed—graffiti and mural, illicit and sanctioned, word and image—in an urban art scene in constant flux.